2011
DOI: 10.1111/j.1469-0691.2011.03510.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison between exogenous and haematogenous periprosthetic joint infections caused by Staphylococcus aureus

Abstract: Patient-related risk factors for invasive Staphylococcus aureus infection overlap with those for periprosthetic joint infections (PJIs). We compared these factors and clinical characteristics between 17 exogenous and 40 haematogenous PJIs caused by S. aureus. Exogenous cases presented significantly more often with damaged periprosthetic soft tissue, whereas haematogenous cases more often had systemic signs of infection, such as fever, chills, and sepsis syndrome. However, comorbid conditions associated with S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 9 publications
2
45
0
1
Order By: Relevance
“…This likely reflects the fact that 90% of the patients in this study were within 3 months of implantation, suggesting that the mechanism of infection initiation dictates some of the clinical presentation. This is corroborated by several studies that found that the presence of soft tissue damage, such as an open wound, sinus tract, or abscess, was more common in patients with contiguous or perioperatively acquired Staphylococcus aureus PJI than in those with hematogenously acquired S. aureus infection (59,63). In contrast, systemic signs or symptoms such as fever or chills were significantly more common in patients with hematogenous PJI.…”
Section: Clinical Manifestationssupporting
confidence: 61%
See 2 more Smart Citations
“…This likely reflects the fact that 90% of the patients in this study were within 3 months of implantation, suggesting that the mechanism of infection initiation dictates some of the clinical presentation. This is corroborated by several studies that found that the presence of soft tissue damage, such as an open wound, sinus tract, or abscess, was more common in patients with contiguous or perioperatively acquired Staphylococcus aureus PJI than in those with hematogenously acquired S. aureus infection (59,63). In contrast, systemic signs or symptoms such as fever or chills were significantly more common in patients with hematogenous PJI.…”
Section: Clinical Manifestationssupporting
confidence: 61%
“…Commonly reported signs or symptoms of PJI include pain, joint swelling or effusion, erythema or warmth around the joint, fever, drainage, or the presence of a sinus tract communicating with the arthroplasty (7,(57)(58)(59). The presence of a sinus tract is considered by most investigators to be definitive evidence of PJI, leading to its inclusion as definitive evidence of PJI in several consensus documents (60)(61)(62), as discussed in Diagnosis, below.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some studies reported seeding from the respiratory, urinary, and gastrointestinal tracts, and dental infections (16). Sendi et al reported that in 57.5% of hematogenous PJI, there was no sign of primary bacteremia or infection during the clinical manifestation; therefore, it is usually difficult to identify the source of infection (17).…”
Section: Classifications Of Pjimentioning
confidence: 99%
“…Nevertheless, some studies reported seeding from the respiratory, urinary and gastrointestinal tracts, and dental infections. 16 Sendi et al 17 reported that in 57.5% of haematogenous PJI, there was no sign of primary bacteraemia or infection during the clinical manifestation; therefore, it is usually difficult to identify the source of infection.…”
Section: Classifications Of Pjimentioning
confidence: 99%